A Balanced Scorecard Design From Key Performance Indicators In An Indonesia Construction Services Company - Sasongko, Fajar (Jurnal Ilmu Sosial Mamangan, 2024)
Construction has become a huge industry in this global era. The lack of a performance management system is the biggest problem that causes unstable performance in this industry. The demand from this industry requires performance measurement and stable management to achieve their vision and mission. There are so many performance measurement tools applied in the construction industry such as Malcolm Baldrige, 6-Sigma, Balanced Scorecard, etc. Balanced Scorecard (BSC) is one of the tools to measure the performance of a company. BSC has 4 (four) perspectives consisting of financial perspective, customer perspective, internal business process perspective, and learning and growth perspective. This article discusses BSC's analysis of construction companies' Key Performance Indicators (KPIs), obtained from annual reports. The company analyzed is a construction service company in Indonesia which is one of the state-owned enterprises (SOEs). There are data limitations which are secondary data from the annual report and BSC analysis based on the company's existing vision, mission, and KPIs. The results of BSC analysis are strategies in terms of finance, customers, internal processes, as well as learning and growth.